Changes in abundance and composition of a Caribbean coral reef zooplankton community after 25 years - Carrillo Baltodano, Allan Martin (2016)
Coral reef zooplankton represents a key community in coral ecosystems, as they are involved in trophic and biogeochemical dynamics, and recruitment processes. Zooplankton abundance, composition and biomass were surveyed at six stations within the coral reef at Cahuita National Park, Limon, Costa Rica, in order to compare with the only previous study conducted during 1984. Samples were collected monthly (September 2010-August 2011). Seston biomass (0.49-85.87 mg/m3) and total abundance (1 145-112 422 ind./m3) fluctuated among the months and the stations. Higher values of these two variables were found in the rainiest months (November 2010 and May 2011). A total of 38 taxa were identified, of which calanoid copepods abundance dominated year round (66 %), followed by appendicularians (12 %). Zooplankton mean abundance in this survey resulted 20 times higher (13 184 ± 4 104 ind./m3)than in 1984 (645 ± 84 ind./m3). Copepods and appendicularians were the groups that differed the most, relative to the 1984 study, resulting in 63 and 170 times more abundant overall, respectively. An increase in terrestrial runoff and nutrient input during the past 30 years could explain these differences. High abundances of zooplankton may constitute an important food source for coral reef organisms in Cahuita ecosystem. In addition, zooplankton abundances here reported for Cahuita are among the worldwide highest coral reef zooplankton abundances, and further trophic models can help elucidate its role in coral reef resilience in the Caribbean Coast of Central America.